Stability analysis of double porous and surface porous layer journal bearing - Rao, T.V.V.L.N. (Maney Publishing, 2016)
The linear stability analysis of double porous and surface porous layer journal bearing based on long and short bearing approximations is presented. The Brinkman model is employed in the porous region and the infinite permeability porous layer is simulated as surface layer. The coefficients of load, threshold speed and critical whirl frequency ratio are computed for double porous and surface porous layer configurations. The coefficients obtained using long and short bearing approximations yield same results. Higher threshold speed is obtained for double layer configurations of (i) high permeability bearing adsorbent porous layer topped with low permeability porous layer, and (ii) surface porous layer lubricant film. Â© 2016 Taylor & Francis.